Mapping of Occupation on Operations Management Within The Indonesian Qualification Framework (IQF) to Close The Gap Between Industry Needs and Educational Outcomes - Surono Surono; Darwin Raja Unggul Saragih (PT. Publikasiku Academic Solution, 2025)
The gap between educational outcomes and industry needs in operations management has become increasingly apparent, highlighting a pressing need for alignment to enhance workforce readiness and national competitiveness. This study aims to identify key competencies required in operations management, map them within the framework of the Indonesian Qualification Framework (IQF), and propose recommendations for aligning educational curricula with industry demands. A qualitative research method was employed, involving literature reviews and expert interviews from both academia and industry sectors to gather data on essential skills, knowledge areas, and role progression in operations management. The findings reveal a comprehensive mapping of occupations within operations management, aligned with the IQF, detailing specific competency standards across different qualification levels—from entry-level to executive roles. The research emphasizes the importance of standardized competency frameworks, industry-relevant curriculum development, stakeholder collaboration, and continuous feedback mechanisms to ensure educational programs remain responsive to evolving market needs. By closing the gap between what is taught and what is required, the study contributes to improving graduate employability and the overall effectiveness of the education-to-employment pipeline in Indonesia. The implications of this research are significant for policymakers, educators, and industry stakeholders in fostering a more integrated, agile, and future-ready workforce. Further studies are recommended to conduct sector-specific analysis and longitudinal assessments of the impact of IQF integration on graduate performance and career progression.